The Case for an Estrogen-iron Axis in Health and Disease - Hamad, Mawieh; Bajbouj, Khuloud; Taneera, Jalal (Experimental and Clinical Endocrinology & Diabetes, 2020)
Clinical and experimental evidence suggest that estrogen manipulates intracellular iron metabolism and that elevated levels of estrogen associate with increased systemic iron availability. This has been attributed to the ability of estrogen to suppress hepcidin synthesis, maintain ferroportin integrity and enhance iron release from iron-absorbing duodenal enterocytes and iron-storing macrophages and hepatocytes. These observations speak of a potential “estrogen-iron” axis that manipulates iron metabolism in response to hematologic (erythropoiesis) and non-hematologic (uterine growth, pregnancy, lactation) needs for iron. Such an axis could contribute to minimizing iron deficiency in premenopausal women and iron overload in postmenopausal women. It could also exacerbate iron overload and related clinical consequences including cancer, osteoporosis, cardiovascular complications and neurodegenerative symptoms, especially in postmenopausal women on hormonal replacement therapy. Understanding the role of estrogen in iron metabolism may shed some light on the pleotropic, but often paradoxical, roles of estrogen in human health and disease.
Keywords: hepcidin; ferritin; ferroportin; hormonal replacement therapy; iron; menopause